Comparison of allocation methods in the life cycle assessment of nickel products - Duan Zhang; Boxue Sun; Suping Cui; Lingqin Meng; Shiwei Du; Zuoren Nie (Journal of Environmental Management, 2026)

Development and application of regionalized characterization factors for resource depletion of individual rare earth elements: a China-specific study - Ying Wang; Wenjuan Chen; Feng Gao; Boxue Sun; Zuoren Nie (The International Journal of Life Cycle Assessment, 2026)

Waste material flows, land use, and environmental impacts of provincial-scale tandem perovskite photovoltaic deployment in China - Zhenguo Wang; Boxue Sun; Yu Liu; Ying Wang; Shiwe Du; Mingyang Li; Feng Gao; Zuoren Nie (Resources, Conservation and Recycling, 2026)

Development and application of an ion-scale chemical exergy method for assessing resource efficiency in hydrometallurgical solution systems - Xingen Lu; Feng Gao; Zuoren Nie; Boxue Sun; Xianzheng Gong; Guoyao Shan (Journal of Environmental Chemical Engineering, 2026)

Life cycle assessment of Chlorination–Electrolysis and conventional aluminum production: environmental insights from low-grade bauxite utilization - Meng Zhao; Boxue Sun; Shiwei Du; Mingyang Li; Yu Liu; Feng Gao; Zuoren Nie (The International Journal of Life Cycle Assessment, 2026)

The determinants of global lithium-ion battery trade network based on temporal exponential random graph model - Chao Wang; Kangyu Tan; Xiaoqian Hu; Boxue Sun; Xianfeng Zhao (Journal of Industrial Ecology, 2026)

Exergy-based resource efficiency evaluation of NdFeB magnet production and recycling in China - Duan Zhang; Boxue Sun; Suping Cui; Lingqin Meng; Shiwei Du; Zuoren Nie (The International Journal of Life Cycle Assessment, 2026)

Life cycle assessment for rare earth production from ion-adsorption deposits: A comparative study of magnesium sulfate and ammonium sulfate leaching techniques - Ying Wang; Feng Gao; Boxue Sun; Wenjuan Chen; Zuoren Nie (Journal of Environmental Management, 2025)

Physicochemical reaction-based allocation for the resource consumption of hydrometallurgical processing of rare-earth oxides—a case study on ion adsorption-type rare-earth oxides in China - Ying Wang; Feng Gao; Boxue Sun; Zuoren Nie (The International Journal of Life Cycle Assessment, 2025)

Integrating sustainability into material design and selection through eco-design: A case study on aluminum alloy plates - Mingyang Li; Feng Gao; Mingzhou Jin; Boxue Sun; Yu Liu; Xianzheng Gong; Zuoren Nie (Journal of Cleaner Production, 2024)

Correction: Characterization of CTBT-Relevant Radioxenon Detections at IMS Stations Using Isotopic Activity Ratio Analysis - Boxue Liu; Martin Kalinowski; Yunwei Sun; Charles R. Carrigan; Christos Saragiotis; Jun Wang; Martin Ertl; Yuichi Kijima; Robin Schoemaker; Jolanta Kuśmierczyk-Michulec; Anne Tipka; Tarabay Antoun (Pure and Applied Geophysics, 2024)

Environmental impact assessment of the manufacture and use of N- type and P-type photovoltaic modules in China - Zhenguo Wang; Yu Liu; Feng Gao; Boxue Sun; Xianzheng Gong; Zuoren Nie (Journal of Cleaner Production, 2024)

Machine learning prediction for constructing a universal multidimensional information library of Panax saponins (ginsenosides) - Hongda Wang; Lin Zhang; Xiaohang Li; Mengxiao Sun; Meiting Jiang; Xiaojian Shi; Xiaoyan Xu; Mengxiang Ding; Boxue Chen; Heshui Yu; Zheng Li; Dean Guo; et al. (Food Chemistry, 2024)

Evolution of structural characteristics and its determinants of global human hair waste trade network based on temporal exponential random graph model - Chao Wang; Xuemei Zhang; Xiaoqian Hu; Boxue Sun; Longfeng Zhao; Ming K. Lim; Qiuyun Zhao; Pezhman Ghadimi (Resources, Conservation and Recycling, 2024)

Ru single-atom regulated Ni(OH)2 nanowires coupled with FeOOH to achieve highly efficient overall water splitting at industrial current density - Boxue Wang; Huachuan Sun; Mingpeng Chen; Tong Zhou; Hongshun Zheng; Mengling Zhang; Bin Xiao; Jianhong Zhao; Yumin Zhang; Jin Zhang; Qingju Liu (Chemical Engineering Journal, 2024)

Synergistic effects of carbon cap-and-trade and renewable portfolio standards on renewable energy diffusion - Xiongping Yue; Chao Wang; Boxue Sun; Huanyu Ren; Yong Tan; Liling Huang; Dan Feng; Xin Li (Journal of Cleaner Production, 2023)

Assessing resource depletion of NCM lithium-ion battery production for electric vehicles: An exergy-based perspective - Shiwei Du; Feng Gao; Zuoren Nie; Yu Liu; Boxue Sun; Xianzheng Gong (Journal of Cleaner Production, 2023)

Life cycle assessment of beneficial use of calcium carbide sludge in cement clinker production: A case study in China - Yu Liu; Yan Zheng; Yanjing Wang; Pinqiao Ren; Boxue Sun; Feng Gao; Xianzheng Gong (Journal of Cleaner Production, 2023)

Mode of innovative green production for concrete engineering: life cycle assessment of accelerators prepared from aluminum mud wastes - Xiao Liu; Hui Xie; Qifeng Luo; Kun Yang; Chunlei Xia; Jianan Guan; Wu Zhou; Boxue Sun; Ziming Wang; Suping Cui (Environmental Science and Pollution Research, 2023)

Characterization of CTBT-Relevant Radioxenon Detections at IMS Stations Using Isotopic Activity Ratio Analysis - Boxue Liu; Martin Kalinowski; Yunwei Sun; Charles R. Carrigan; Christos Saragiotis; Jun Wang; Martin Ertl; Yuichi Kijima; Robin Schoemaker; Jolanta Kuśmierczyk-Michulec; Anne Tipka; Tarabay Antoun (Pure and Applied Geophysics, 2023)
Radioxenon isotopes measured at radionuclide stations of the Comprehensive Nuclear-Test-Ban Treaty’s (CTBT) International Monitoring System (IMS) may indicate releases from underground nuclear explosions (UNEs) but are often caused by emissions from nuclear facilities. Characterization of CTBT-relevant nuclear events may use the evolution of isotopic activity ratios over time, which goes from the release of an assumed UNE, through atmospheric transport, to sample collections and measurements. A mathematical approach is presented to discuss the characterization of the spatial and temporal relationships between a nuclear explosion and radioxenon measurements. On the one hand, activity concentrations at an IMS station are estimated by using the assumed release scenario regarding a UNE and atmospheric transport modelling. On the other hand, the activities collected in the samples are determined by spectral analysis first and the activity concentrations in the air passing over the IMS station are estimated under an assumption of constant concentration during sampling. The isotopic ratios of activities released from the UNE are related to the isotopic ratios of activity concentrations in the plume of air crossing the IMS station, resulting in a function of the isotopic activity ratio over the time from detonation to sample measurement. The latter is used for discrimination of a nuclear test and estimation of the time of detonation, such as a four radioxenon plot of the activity ratio relationship of 135 Xe/ 133 Xe versus 133m Xe/ 131m Xe.

Impacts of China’s exports decline in rare earth primary materials from a trade network-based perspective - Xiaoqian Hu; Boxue Sun; Chao Wang; Ming K. Lim; Peng Wang; Xinyi Geng; Cuiyou Yao; Wei-Qiang Chen (Resources Policy, 2023)

Life cycle assessment of regeneration technology routes for sintered NdFeB magnets - Ying Wang; Boxue Sun; Feng Gao; Wenjuan Chen; Zuoren Nie (The International Journal of Life Cycle Assessment, 2022)

Exergy-based resource consumption analysis of cement clinker production using natural mineral and using calcium carbide sludge (CCS) as raw material in China - Boxue Sun; Yu Liu; Zuoren Nie; Feng Gao; Zhihong Wang; Suping Cui (The International Journal of Life Cycle Assessment, 2020)

Physical parameter-based allocation for the energy consumption of pyro-metallurgical system—a case study on nickel production in China - Boxue Sun; Yu Liu; Zuoren Nie; Feng Gao; Zhihong Wang; Xianzheng Gong (The International Journal of Life Cycle Assessment, 2017)

Cumulative exergy demand analysis of the primary aluminum produced in China and its natural resource-saving potential in transportation - Boxue Sun; Zuoren Nie; Feng Gao; Yu Liu; Zhihong Wang; Xianzheng Gong (The International Journal of Life Cycle Assessment, 2015)